Correlation functions in scalar field theory at large charge - G. Arias-Tamargo; D. Rodriguez-Gomez; J. G. Russo (Journal of High Energy Physics, 2020)
Abstract We compute general higher-point functions in the sector of large charge operators ϕn, ϕ ¯ n $$ {\overline{φ}}^n $$ at large charge in O(2) ϕ ¯ ϕ 2 $$ {\left(\overline{φ}φ \right)}^2 $$ theory. We find that there is a special class of “extremal” correlators having only one insertion of ϕ ¯ n $$ {\overline{φ}}^n $$ that have a remarkably simple form in the double-scaling limit n →∞ at fixed g n2 ≡ λ, where g ~ ϵ is the coupling at the O(2) Wilson-Fisher fixed point in 4 − ϵ dimensions. In this limit, also non-extremal correlators can be computed. As an example, we give the complete formula for ϕ x 1 n ϕ x 2 n ϕ ¯ x 3 n ϕ ¯ x 4 n $$ \left\langle φ {\left({x}_1\right)}^nφ {\left({x}_2\right)}^n\overline{φ}{\left({x}_3\right)}^n\overline{φ}{\left({x}_4\right)}^n\right\rangle $$ , which reveals an interesting structure.